A Nucleolar Isoform of the Drosophila Ubiquitin Specific Protease dUSP36 Regulates MYC-Dependent Cell Growth - Thevenon, Dominique; Seffouh, Ilham; Pillet, Catherine; Crespo-Yanez, Xenia; Fauvarque, Marie-Odile; Taillebourg, Emmanuel (Frontiers in Cell and Developmental Biology, 2020)
The c-Myc oncogene is a transcription factor that regulates the expression of a very large set of genes mainly involved in cell growth and proliferation. It is overexpressed in more than 70% of human cancers, illustrating the importance of keeping its levels and activity under control. The ubiquitin proteasome system is a major regulator of MYC levels in humans as well as in model organisms such as Drosophila melanogaster. Although the E3 ligases that promote MYC ubiquitination have been largely investigated, the identity and the role of the deubiquitinating enzymes, which counteract their action is only beginning to be unraveled. Using isoform-specific CRISPR-Cas9 mutagenesis, we show that the Drosophila homolog of the Ubiquitin Specific Protease USP36 has different isoforms with specific sub-cellular localizations and that the nucleolar dUSP36-D isoform is specifically required for cell and organismal growth. We also demonstrate that this isoform interacts with dMYC and the E3 ligase AGO and regulates their stability and ubiquitination levels. Furthermore, we show that dUSP36 is ubiquitinated by AGO and is able to self-deubiquitinate. Finally, we provide in vivo evidence supporting the functional relevance of these regulatory relationships. Together these results reveal that dMYC, AGO and dUSP36 form a tripartite, evolutionary conserved complex that acts as a regulatory node to control dMYC protein levels.